2006
DOI: 10.2119/2006-00014.hendricks
|View full text |Cite
|
Sign up to set email alerts
|

Predifferentiated Embryonic Stem Cells Prevent Chronic Pain Behaviors and Restore Sensory Function Following Spinal Cord Injury in Mice

Abstract: Embryonic stem (ES) cells have been investigated in repair of the CNS following neuronal injury and disease; however, the efficacy of these cells in treatment of postinjury pain is far from clear. In this study, we evaluated the therapeutic potential of predifferentiated mouse ES cells to restore sensory deficits following spinal cord injury (SCI) in mice. The pain model used unilateral intraspinal injection of quisqualic acid (QUIS) into the dorsal horn between vertebral levels T13 and L1. Seven days later, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 59 publications
2
31
0
Order By: Relevance
“…Although the reasons for reduced GABA signaling after peripheral or central nerve injury are still matter of debate (57,58,60), several studies showed that transplantation of GABA-releasing cells is an effective way to reduce neuropathic pain symptoms in experimental models of pain (7,22,23,38,43,54,71,74). The findings in our lab suggest that the positive effects of neural progenitor grafts are likely mediated, at least in part, by releasing GABA in the dorsal horn, as both antinociceptive effects and attenuated dorsal horn hyperexcitability by NPC grafts were reduced by GABAergic antagonists (42,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the reasons for reduced GABA signaling after peripheral or central nerve injury are still matter of debate (57,58,60), several studies showed that transplantation of GABA-releasing cells is an effective way to reduce neuropathic pain symptoms in experimental models of pain (7,22,23,38,43,54,71,74). The findings in our lab suggest that the positive effects of neural progenitor grafts are likely mediated, at least in part, by releasing GABA in the dorsal horn, as both antinociceptive effects and attenuated dorsal horn hyperexcitability by NPC grafts were reduced by GABAergic antagonists (42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional GABA signaling is thought to contribute to chronic pain, and GABAergic neural progenitor cells (NPCs) have shown promise in reducing neuropathic pain behavior following transplantation in rat and mouse pain models (7,38,46,52,54). Previous studies in our laboratory showed amelioration of neuropathic pain in rats induced by either peripheral nerve injury or spinal cord injury by intraspinal GABAergic NPC grafts (42,43,48,49).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, intravenous administration of MSCs was able to increase the expression of some growth factors, such as nerve growth factor (NGF) and brain-derived neurotrophic factor (BDNF), in the rat brain after traumatic brain injury [41]. Similarly, it has been shown that transplantation of pre-differentiated embryonic stem (ES) cells into neuronal progenitors is able to prevent the appearance of chronic pain in an experimental model of spinal cord injury in mice [42]. These pre-differentiated ES cells activate both BDNF and IL-6 signaling pathways in the host tissue leading to activation of cAMP/PKA, phosporylation of cofilin and synapsin I, and promotion of regenerative growth and neuronal survival [43].…”
Section: Discussionmentioning
confidence: 99%
“…The injection of saline vehicle was chosen as control to avoid any potential confounding effects that may result from release of trophic factors or other active agents by control cellular transplants. The use of vehicle or cell culture media as control has been previously employed in other transplantation studies (Hendricks, et al, 2006, McDonald, et al, 1999, Mitsui, et al, 2003, Park, et al, 2010, Zhao, et al, 2004). After injection, the pipette was kept in place for additional 1 min.…”
Section: Methodsmentioning
confidence: 99%